Clinical Study on Management and Outcome of Perforated Appendicitis in a Tertiary Level Hospital in Bangladesh (Community Based Medical Journal, 2026)
Perforated appendicitis remains a significant surgical emergency in developing countries. Understanding its clinical profile and outcomes is crucial for improving management in resource-limited settings like Bangladesh. A cross-sectional, descriptive study was conducted in the Department of Surgery, Mymensingh Medical College Hospital, Mymensingh, Bangladesh, between October 2013 and March 2014, to analyze the clinical presentation, management, and outcomes of perforated appendicitis in a tertiary hospital. Our study included 100 intraoperatively confirmed perforated appendicitis cases among 759 acute appendicitis admissions. Data on demographics, clinical features, management, and outcomes were analyzed. Perforation rates were highest in children 3 days) occurred in 85% of cases. All patients received IV antibiotics (95% metronidazole, 75% ceftriaxone), and 98% underwent appendectomy. Postoperative complications included wound infection (25%) and intra-abdominal abscess (10%). Mean hospital stay was prolonged (45% required 8-10 days of hospitalization). Delayed presentation significantly contributed to perforation rates. Despite complications, prompt surgery and antibiotics yielded favorable outcomes, underscoring the importance of early intervention strategies in resource-limited settings.  CBMJ 2026 January: vol. 15 no. 01 P:89-95